Desarrollo de producto que optimice el aprendizaje del kitesurf, para usuarios en nivel principiante (2010)
Elaprendizajedelkitesurfsereduceadesarrollarlacapacidaddeunpracticanteairencontradelviento,paraquedetalforma,elmismopuedanavegarmedianteelusodeunacometadetracciónokite,sobreunatabladiseñadaparatalefecto,enladirecciónqueelusuariodesee,partiendodeunpuntoenlaplaya,lagoorepresayregresandoalmismopuntounavezfinalizadalapráctica,adichamaniobraseledenominacomoorzadodentrodellenguajekitesurfista.Unavezqueelusuariopuedenavegarentodaslasdireccionesyllegaralmismopuntodedondepartió,sepuededecirqueelkiteropracticante,dominalosequiposnecesariosparalapracticadeestedeporte,asícomolatécnicanecesariaparaeldesarrollodelmismo,enestepuntoelusuariodejadeserprincipianteycomienzaaserintermedioiniciandounaetapaenlaqueseaprendendeterminadonumerodetrucosconlatablaylacometa. Asípues,miproyectopretendeoptimizarelaprendizajedelkitesurfdesarrollandounnuevoproducto,quepretendeintervenirenelprocesodeaprendizajeconsiguiendoqueelusuariomemoriceydesarrolle,posturasymovimientosóptimosparaorzaryderivarmientrasnavegaynoqueloaprendaempíricamentemientraslodescubre,comosucedeactualmenteenelaprendizajedelkitesurf.